Identification of the Impact Resulting from the Scarcity of Cooking Oil and the Fluctuations of People's Purchasing Power on the Products Produced by the Food Industry in the City of Makassar - Nahriana (International Journal of Integrative Sciences, 2023)
The purpose of this study is to identify the impact produced from the scarcity of cooking oil and community purchasing power fluctuations on the products produced by the food industry in Makassar City. For this reason, this study uses a quantitative approach, and sampling in this study uses purposive sampling techniques that is a sample determination technique based on the consideration of researchers regarding which samples are most suitable, useful and are considered to represent a population. This variable, can be measured using an instrument, so that the amount of data can be analyzed using statistical procedures